Measurement properties of the incremental step test for people with chronic obstructive pulmonary disease: a cross-sectional study - Gonçalves, T (2024)
Objectives: The new incremental step test (IST) is a field test that was developed for people with chronic obstructive pulmonary disease (COPD), based on the characteristics of the incremental shuttle walk test (ISWT); however, its measurement properties still need to be determined. We aimed, first, to assess the construct validity (through the comparison with the ISWT), within-day reliability and measurement error of the IST in people with COPD; and, second, to identify whether the participants have a learning effect in the IST. Design: Cross-sectional study, conducted according to COnsensus-based Standards for the selection of health status Measurement INstruments guidelines. Setting: A family health unit in Portugal, April 2022 to June 2023. Participants and analysis: 63 participants (67.5±10.5 years) attended two sessions to perform two IST and two ISWT, separately. Spearman's correlations were used to compare the best performances between the IST and the ISWT. Intraclass correlation coefficient (ICC2,1) was used for reliability, and the SE of measurement (SEM), minimal detectable change at 95% CI (MDC95) and Bland and Altman 95% limits of agreement (LoA) were used for measurement error. The learning effect was explored with the Wilcoxon signed-rank test. Results: The IST was significant and strongly correlated with the ISWT (0.72<ρ<0.74, p<0.001), presented an ICC2,1 of 0.95 (95% CI 0.92 to 0.97), SEM=11.7 (18.9%), MDC95=32.4 (52.2%) and the LoA were -33.61 to 31.48 for the number of steps. No difference was observed between the number of steps of the two attempts of the IST (p>0.05). Conclusions: The IST can be suggested as a valid and reliable test to assess exercise capacity in people with COPD, with no learning effect when two IST are performed on the same day. The measurement error of the IST is considered indeterminate.